Pendidikan Anak dalam Keluarga Perspektif Al-Quran - Firman Heryana; Ilyas Rifa'i (ISLAMICA, 2022)
The purpose of this study is to identify that the family has an important role in children's education, namely shaping the character of a child. Families have complementary components. Good and bad are not inherited through blood relationships and good families originate from good individuals. This research uses an empirical sociological approach method that is descriptive analysis with the use of qualitative data as the type of research and library research as one of the data collection techniques. This research concludes that there are four scopes as the basis of religious education in the family, namely aqidah, moral, social and emotional. Furthermore, the pattern of children's education during the Jahiliyah Arab and Islamic periods had very significant differences, including differences in justice for boys and girls. So that the orientation of Islamic education is to become a devout human being, that is, to live all His commandments and stay away from all His prohibitions.